Probing Charge Management across the π-Systems of Nanographenes in Regioisomeric Electron Donor-Acceptor Architectures - Hölzel, Helen; Haines, Philipp; Kaur, Ramandeep; Lungerich, Dominik; Jux, Norbert; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Inspired by light-induced processes in nature to mimic the primary events in the photosynthetic reaction centers, novel functional materials combine electron donors and acceptors, i.e., (metallo)porphyrins (ZnP) and fullerenes (C60), respectively, with emerging materials, i.e., nanographenes. We utilized hexa-peri-hexabenzocoronene (HBC) due to its versatility regarding functionalization and physicochemical properties, to construct three regioisomeric ZnP-HBC-C60 conjugates, which foster geometrical diversity by arranging ZnP and C60 in ortho-, meta-, and para-positions to each other. The corresponding hexaarylbenzene (HAB) motifs, with an interrupted π-system, were also prepared. Transient absorption measurements disclosed the fast population of charge transfer as well as singlet and triplet charge-separated states. With the help of density functional theory (DFT) calculations, we further conceive the communication across the HBCs and HABs. This work reveals the impact of both the geometrical arrangement with respect to through-space versus through-bond interactions and the structural rigidity/flexibility on the charge management across the different π-systems.
CRIS-Team Scopus Importer:2022-06-10